2016
DOI: 10.1088/0964-1726/25/10/105012
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing technology of integrated textile-based sensor networks forin situmonitoring applications of composite wind turbine blades

Abstract: Based on in situ strain sensors consisting of piezo-resistive carbon filament yarns (CFYs), which have been successfully integrated into textile reinforcement structures during their textiletechnological manufacturing process, a continuous load of fibre-reinforced plastic (FRP) components has been realised. These sensors are also suitable for structural health monitoring (SHM) applications. The two-dimensional sensor layout is made feasible by the usage of a modular warp yarn path manipulation unit. Using a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Previous examinations made by the authors showed that CF is suitable as an in situ strain gage for the structural and strain monitoring of fiber-reinforced plastic components. 1619
Figure 3.Measurement principle of carbon fiber (CF)-based textile strain gages (a) and method for the determination of specific sensor values (b).
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous examinations made by the authors showed that CF is suitable as an in situ strain gage for the structural and strain monitoring of fiber-reinforced plastic components. 1619
Figure 3.Measurement principle of carbon fiber (CF)-based textile strain gages (a) and method for the determination of specific sensor values (b).
…”
Section: Methodsmentioning
confidence: 99%
“…Previous examinations made by the authors showed that CF is suitable as an in situ strain gage for the structural and strain monitoring of fiber-reinforced plastic components. [16][17][18][19] For the purpose of comparison, the typical sensor characteristic values, which apply to strain gages (cf. Figure 3(b)), were used: the gage factor k (Equation (3)), the linearity deviation A Lin (Equation 4) from an assumed linear transfer characteristic curve and the hysteresis A Hys (Equation 5).…”
Section: Resistive Fiber Sensorsmentioning
confidence: 99%
“…6, a good correlation between applied loads, calculated strain and measured sensor signals is achieved. For further information, please refer to [3][4]. With the use of functional, biocompatible materials like viscose or chitosan moisture or pH-sensor yarns based on the coaxial sensor set-up for impedimetric measurements as shown in Fig.…”
Section: Fig 4 Functional Frp-demonstrator Of Wind Turbine Blade Wimentioning
confidence: 99%
“…According to the state of the art, metallized fibers, carbon fibers, or fine copper wires are commonly used to conduct electric current [ 21 , 22 , 23 ]. These materials feature very low electrical resistances as well as several specific disadvantages: metal-based conductors are generally characterized by a very low elongation at break and almost no elastic strain [ 24 ].…”
Section: Introductionmentioning
confidence: 99%